2015
DOI: 10.1007/s00449-015-1436-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of biologically synthesized silver nanoparticles against food- and water-borne microbes

Abstract: In the present study, silver nanoparticles (AgNPs) synthesized from aqueous leaves extract of Malva crispa and their mode of interaction with food- and water-borne microbes were investigated. Formation of AgNPs was conformed through UV-Vis, FE-SEM, EDS, AFM, and HR-TEM analyses. Further the concentration of silver (Ag) in the reaction mixture was conformed through ICP-MS analysis. Different concentration of nanoparticles (1-3 mM) tested to know the inhibitory effect of bacterial pathogens such as Bacillus cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Best particle formation occurred at pH 10. Using alkaline pH for AgNPs synthesis is also reported by [22].…”
Section: Resultsmentioning
confidence: 94%
“…Best particle formation occurred at pH 10. Using alkaline pH for AgNPs synthesis is also reported by [22].…”
Section: Resultsmentioning
confidence: 94%
“…Table S1 provides data on the in vitro genotoxic effects of biogenic NPs for each biological source used to synthesize MNPs and Table S2 shows the in vivo genotoxicity outcomes. Although several studies reported no genotoxicity [24,25,26,27,28,29,30,31,32] or antigenotoxic activity [24,33,34,35,36] of biogenic MNPs, most of the studies reported genotoxic effects at specific concentrations and with a dose or time dependence.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of nanoparticles of precious metals (or their oxides) using Malva species extracts has been reported by many groups. [140][141][142]172,188,216,[303][304] In all these reports, aqueous extracts of leaves or flowers of the plants were used. The major quality that enables this kind of uses and reactions is the fact that these extracts are rich in flavonoids and anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…These were tested against various pathogen bacteria and found effective. 141 They were also highly toxic for zebra fish (Danio rerio) 142 …”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%